2021
DOI: 10.1017/s1368980021004456
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition education strategies to promote vegetable consumption in preschool children: the Veggies4myHeart project

Abstract: Objective: To test the efficacy of three nutrition education strategies on the intake of different vegetables in preschool children. Design: This is an experimental study conducted in four Portuguese preschools. The intervention consisted of 20-min educational sessions, once a week, for 5 weeks, with one of the following randomised educational strategies: Portuguese Food Wheel Guide (control), digital game, storybook, storybook and reward (stickers). All groups had repeated exposure to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…After 3 minutes arrived in the holding area, children were given various stickers to choose from, and quite a few children accepted what they chose gladly at the very start, Interestingly, at the time of oral midazolam administration, some of them cried loudly or refused vehemently, which was the same as the ndings of the study about the implementation of nutrition education strategies to promote vegetable consumption in preschool children [15]. In that study, the use of stickers was shown advantage in the short term, but it was not effective subsequently.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…After 3 minutes arrived in the holding area, children were given various stickers to choose from, and quite a few children accepted what they chose gladly at the very start, Interestingly, at the time of oral midazolam administration, some of them cried loudly or refused vehemently, which was the same as the ndings of the study about the implementation of nutrition education strategies to promote vegetable consumption in preschool children [15]. In that study, the use of stickers was shown advantage in the short term, but it was not effective subsequently.…”
Section: Discussionmentioning
confidence: 86%
“…A Portugal study found that preschool children who received a sticker as a reward could promote vegetable consumption [15]. Another study reported that pediatric dentists used a sticker as one of the rewards to encourage their young patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…The first study to test the Veggies4myHeart video game was conducted in Portugal. In a preschool, the video game combined with repeated tasting was compared with the use of a storybook and repeated tasting with or without sticker rewards and a control group [ 17 ]. After the intervention and at a 6-month follow-up, children in all groups, including the control group, had increased their vegetable consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The Veggies4myHeart digital game was developed by a team of researchers at the Polytechnic of Leiria in Portugal [ 17 ]. The digital game was designed for preschool children aged 3-6 years and consists of 5 mini games, each related to one of the following vegetables: carrot, tomato, lettuce, cucumber, and red cabbage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation